2022
DOI: 10.1007/s10439-022-02914-3
|View full text |Cite
|
Sign up to set email alerts
|

Head Impact Exposure and Biomechanics in University Varsity Women’s Soccer

Abstract: Soccer is a unique sport where players purposefully and voluntarily use their unprotected heads to manipulate the direction of the ball. There are limited soccer head impact exposure data to further study brain injury risks. The objective of the current study was to combine validated mouthpiece sensors with comprehensive video analysis methods to characterize head impact exposure and biomechanics in university varsity women’s soccer. Thirteen female soccer athletes were instrumented with mouthpiece sensors to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 51 publications
2
21
2
Order By: Relevance
“…A previous study on head impact exposure per AE in footballers reported rates of 1.83 and 3.19 among female and male players, respectively. 11,15 The values of head impact exposure were higher in the current study than in previous studies involving athletes without disabilities, indicating that head impact frequency increased with visual impairment. We found that blind football players exhibited a high head impact frequency even though they did not head the ball.…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…A previous study on head impact exposure per AE in footballers reported rates of 1.83 and 3.19 among female and male players, respectively. 11,15 The values of head impact exposure were higher in the current study than in previous studies involving athletes without disabilities, indicating that head impact frequency increased with visual impairment. We found that blind football players exhibited a high head impact frequency even though they did not head the ball.…”
Section: Discussioncontrasting
confidence: 73%
“…The development of effective headgear and verification of its effectiveness are expected in the future. A previous study on head impact exposure per AE in footballers reported rates of 1.83 and 3.19 among female and male players, respectively 11,15 . The values of head impact exposure were higher in the current study than in previous studies involving athletes without disabilities, indicating that head impact frequency increased with visual impairment.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Therefore, instrumented mouthguards (iMGs) show substantial promise for improving accuracy in real-time measurement of HAE in field sports 9–12. The data collected can be used to improve player welfare by informing decisions regarding training loads 6 13. For clinicians and sports scientists, the hope is that real-time on-field evaluation of head impacts will lead to earlier detection of potential injurious events, support earlier medical intervention and removal from play for at-risk players 14…”
Section: Introductionmentioning
confidence: 99%